Bridging Knowledge And Business: Education And Entrepreneurial Development - Đoković, Goran; Jovanović, Saša; Čelik, Petar (Industrija, 2025)
Abstract: Considering the growing importance of entrepreneurship and its far-reaching contributions across various sectors, this paper aims to emphasize the role of education in fostering the acquisition of knowledge and skills essential for developing entrepreneurial mindsets and practices. It also highlights the positive impact that developing entrepreneurial competencies can have on students. The research combines an in-depth literature review of relevant studies on entrepreneurial education with an empirical survey investigating graduate students’ attitudes from the Republic of Serbia. Data analysis and interpretation included descriptive statistics, correlation method and regression model. The findings demonstrated that entrepreneurial teaching and support significantly affect entrepreneurial impact such as skills to manage risk, entrepreneurial mindst and ability to create value for others. Keywords: entrepreneurship, entrepreneurial education, entrepreneurial competencies, entrepreneurial mindset